Assessment of the potential genotoxicity and phototoxicity of triazine UV filters - Yilian Wei; Meng Xiang; Jinyu Dong; Zhigang Wang; Xuan Wang; Hao Liu; Jianjun Liu; Wenli Xu; Jie Li; Yibei Zhan (Journal of Dermatologic Science and Cosmetic Technology, 2025)
Background: Ethylhexyl triazone (EHT) and diethylhexyl butamido triazone (HEB) both belong to the recently developed class of triazine ultraviolet filters. However, their toxicity profiles remain unclear. Objective: To assess the genotoxic and phototoxic effects of EHT and HEB. Methods: The genotoxicity of EHT and HEB was assessed using in vitro bacterial reverse mutation assays, chromosomal aberration assays, and micronucleus assays. Meanwhile, their phototoxicity was evaluated using in vitro 3T3 neutral red uptake (NRU) phototoxicity assays and in vivo skin phototoxicity tests. Results: In the bacterial reverse mutation assay, the number of bacterial colonies was not significantly higher in the EHT and HEB groups than in the solvent control group. Similarly, the chromosomal aberration assay revealed no increase in aberration rates after either EHT or HEB treatment. In the micronucleus assay, the frequency of micronuclei was comparable between the treatment and control groups. Finally, based on the 3T3 NRU phototoxicity assay, both EHT and HEB (photo-irritation factor < 2 and mean photo effect value < 0.1) were classified as non-phototoxic. The skin phototoxicity test in vivo showed the same results as in vitro. Conclusion: Results from a series of genotoxicity and phototoxicity assays indicate that EHT and HEB possess neither genotoxic nor phototoxic potential. These findings provide experimental evidence supporting the safety of EHT and HEB for topical applications.